Speakers of Different Languages Process the Visual World Differently - Chabal, Sarah (J Exp Psychol Gen, 2015)
Language and vision are highly interactive. Here we show that people activate language when they perceive the visual world, and that this language information impacts how speakers of different languages focus their attention. For example, when searching for an item (e.g., clock) in the same visual display, English and Spanish speakers look at different objects. Whereas English speakers searching for the clock also look at a cloud, Spanish speakers searching for the clock also look at a gift, because the Spanish names for gift (regalo) and clock (reloj) overlap phonologically. These different looking patterns emerge despite an absence of direct linguistic input, showing that language is automatically activated by visual scene processing. We conclude that the varying linguistic information available to speakers of different languages affects visual perception, leading to differences in how the visual world is processed.